Networking dan Mobilisasi Massa Puri dalam Pemilukada Kabupaten Klungkung Tahun 2013 - Pratama, Raenaldy Yogi; Bandiyah, Bandiyah; Mahaswari Jayanthi Mertha, Anak Agung Sagung Mirah (Jurnal Nawala Politika, 2020)
ABSTRACT P olitical parties in Klungkung regencyoften takecandidate from the Puri Klungkung from is seen year to year. This study aims toprovide factors causing the interest of political parties to take Puri Klungkung figure as candidate in Klungkung District Election 2013. This research use d qualitative methods, data collection done through observation and interviews. The object in this studyare the Golkar Party DPC, the PDI-P DPC , Former Chairman of KPU Klungkung period 2008-2013 and Puri candidate in local election 2013. Based results analysis, political parties tendency taking Puri Klungkung figures ascandidate in Klungkung District Election2013 influenced by several factors i.e.,Puri Klungkung is still active in politics from royal era until now, Puri figure has charisma of a king, Puri Klungkung plays important role s insocial life people in Klungkung and the transparency of Puri Klungkung in politics facilitates Puri figure taken as candidates by political parties .   Keywords : Networking,Puri Klungkung, District election .